Deploying Reliable IPv6 Temporary Networks Thanks to NEMO Basic Support and Multiple Care-of Addresses Registration - Kuntz, R. (2007 International Symposium on Applications and the Internet Workshops, 2007)
In this paper, we explain how an IPv6 temporary network can be easily deployed using NEMO basic support, while keeping usual network requirements such as load balancing and fault-tolerance using multiple care-of addresses registration, and easy administration with policy exchange mechanisms. We detail a scenario and its feasibility is endorsed by the results obtained in a real deployment